Platelet Toll-like receptor expression and activation induced by lipopolysaccharide and sepsis. (3rd April 2019) - Claushuis, Theodora A.M.; Van Der Veen, Annelou I.P.; Horn, Janneke; Schultz, Marcus J.; Houtkooper, Riekelt H.; Van 'T Veer, Cornelis; Van Der Poll, Tom
Abstract: Platelets and Toll-like receptor (TLR) signalling play a role in the immune response during sepsis. Although preclinical knowledge about the role of platelet TLR signalling is increasing, data during human sepsis are less abundant. Moreover, controversy remains about the effect of the TLR4 agonist lipopolysaccharide (LPS) on platelet activation. We therefore assessed platelet TLR expression during human and murine sepsis. Moreover, we investigated the effect of TLR4 signalling on platelet activation and TLR expression. Platelets from healthy controls stimulated with LPS did not show classical platelet activation (P-selectin, CD63 and phosphatidylserine expression), potentiation of subthreshold agonist stimulation nor platelet-leukocyte complex formation. LPS stimulation however did increase maximal mitochondrial respiration in a TLR4-dependent manner. Platelet stimulation with LPS did not alter TLR expression. Platelet stimulation with thrombin receptor activating peptide increased TLR5 and TLR9, but not TLR2 or TLR4 expression. Platelets from patients with sepsis and mice with experimental sepsis showed platelet activation, but unaltered TLR expression. These results indicate that sepsis-induced platelet activation is not associated with altered platelet TLR expression and, although platelets are responsive to LPS, stimulation of platelet TLR4 does not result in classical platelet activation.